Energetics and Redox Kinetics of Pure Ferrocene-Terminated N-Heterocyclic Carbene Self-Assembled Monolayers on Gold - Qi, Lin (Langmuir : the ACS journal of surfaces and colloids, 2024)
N-heterocyclic carbene (NHC) self-assembled monolayers (SAMs) on gold have received considerable attention, but little is known about the lateral interactions between neighboring NHC molecules, their stability when subjected to aggressive oxidizing/reducing conditions, and their interactions with solution ions, all of which are essential for their use in a wide range of applications. To address these deficiencies, we present a comprehensive investigation of two different ferrocene (Fc)-terminated NHC SAMs with different chain lengths and linking groups. Pure monolayers of Fc-terminated NHCs display only a single, symmetrical pair of redox peaks, implying the formation of a homogeneous SAM structure with uniformly distributed Fc/Fc+ redox centers. By comparison, pure Fc-alkylthiol SAMs exhibit complex and impractical redox chemistry and require surface dilution in order to achieve reproducible properties. The NHC SAMs examined in this study exhibit very fast Fc redox kinetics and comparable or even superior stability against the application of multiple potential cycles or long-time holding at constant potential compared to alkylthiol SAMs. Furthermore, ion pairing of Fc+ and hydrophobic perchlorate and other hydrophilic anions is observed with Fc-NHC SAMs, highlighting conditions favorable for future applications of these monolayers. This study should therefore shed light on the very promising characteristics of redox-active NHC SAMs as an alternative to traditional Fc-alkylthiol SAMs for multiple practical applications, including in sensors and electrocatalysis